Femtosecond near edge x-ray absorption measurement of the VO2 phase transition. - Cavalleri, A; Chong, H; Fourmaux, S; Glover, T; Heimannn, P; Kieffer, J; Padmore, H; Schoenlein, R (2005)
We measure the insulator-to-metal transition in VO2 using femtosecond Near-Edge X-ray Absorption. Sliced pulses of synchrotron radiation are used to detect the photo-induced dynamics at the 516-eV Vanadium L-3 edge.